A kind of fluorocarbon powder coating and preparation method thereof

By using a variety of resins to compound and adding nanotitanium dioxide, glass fiber staple fiber and graphene oxide in fluorocarbon powder coating, the problem of insufficient long-term adhesion of fluorocarbon powder coating on aluminum alloy substrates is solved, and the density and adhesion of the paint film are significantly improved.

CN118580728BActive Publication Date: 2025-03-14JIANGXI DEFUSHENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410690495.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-30
Publication Date
2025-03-14
Estimated Expiration
2044-05-30

AI Technical Summary

Technical Problem

The long-term adhesion of existing fluorocarbon powder coatings on aluminum alloy substrates is poor, which affects its application range and performance.

Method used

By combining a variety of resins with fluorocarbon resin, including acrylic resin, polyester resin and fluorocarbon resin, the paint film toughness of fluorocarbon resin after filming on the surface of the aluminum alloy substrate is regulated, and nanotitanium dioxide, glass fiber staple fiber and graphene oxide are added to the composite resin system to improve the density and adhesion of the paint film.

Benefits of technology

It significantly improves the long-term adhesion of fluorocarbon powder coating on aluminum alloy substrates, enhances the density and water resistance of the paint film, and ensures that the coating is not easily peeled off or damaged during long-term use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of powder coatings. More specifically, it relates to a fluorocarbon powder coating and a preparation method thereof. The product prepared by the present invention comprises the following raw materials in parts by weight: 60-65 parts of fluorocarbon resin, 20-25 parts of acrylic resin, and 10-15 parts of polyester resin, wherein nano titanium dioxide particles are dispersed in the fluorocarbon resin; glass fiber staple fibers are dispersed in the acrylic resin; graphene oxide is dispersed in the polyester resin; the nano titanium dioxide particles are quasi-spherical nano titanium dioxide, and the D50 of the nano titanium dioxide particles is 10-20nm; the aspect ratio of the glass fiber staple fibers is 10:1-15:1, and the average length is 1.2-1.8mm; the D50 of the graphene oxide is 80-150nm. The sphericity of the quasi-spherical nano titanium dioxide is 8.0-8.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of powder coatings, and more specifically, relates to a fluorocarbon powder coating and a preparation method thereof. Background Art

[0002] Fluorocarbon powder coating is a high-performance coating with many significant advantages. It is widely used in architectural aluminum profiles, steel structure buildings, bridges, ships, rail vehicles, pipelines, chemical facilities and other fields. Fluorocarbon powder coatings can generally be divided into thermoplastic fluorocarbon powder coatings: based on FEVE (fluorocarbon resin), PVDF (polyvinylidene fluoride), ETFE (ethylene-tetrafluoroethylene copolymer), ECTFE (ethylene-chlorotrifluoroethylene copolymer) and other resins, made by different preparation methods such as emulsion precipitation and melt extrusion; thermosetting fluorocarbon powder coatings: based on chlorotrifluoroethylene / tetrafluoroethylene and vinyl ether or vinyl ester copolymers and their curing agents, the finished product is obtained by premixing-melt extrusion-crushing-screening.

[0003] With the strengthening of environmental protection regulations, the use of solvent-based fluorocarbon coatings has been restricted, and water-based FEVE fluorocarbon dispersion coatings and powder coatings have gradually become dominant due to their environmental protection characteristics. Powder coatings are expected to be more widely used in the future due to their advantages in construction performance, energy saving and consumption reduction.

[0004] However, at present, fluorocarbon powder coatings still have many technical problems. For example, the problem of water permeability resistance. At present, many fluorocarbon coatings have insufficient density after curing, resulting in poor water permeability resistance, which needs to be improved by increasing the cross-linking degree of the coating or adding specific chemicals; yellowing problem. Fluorocarbon powder coatings are prone to yellow edges during the curing process, which affects the appearance and performance of the coating; adhesion problem. Pure fluorocarbon powder coatings have poor adhesion on aluminum alloy substrates, which limits its application range. Although impact resistance can be improved by adding toughening resins or rubber bodies, the long-term adhesion of the coating to the substrate is still one of the challenges faced by technical personnel in this field. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the problem of poor long-term adhesion of existing fluorocarbon powder coatings to aluminum alloy substrates, and provide a fluorocarbon powder coating and a preparation method thereof.

[0006] The purpose of the present invention is to provide a fluorocarbon powder coating.

[0007] Another object of the present invention is to provide a method for preparing a fluorocarbon powder coating.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A fluorocarbon powder coating comprises the following raw materials in parts by weight:

[0010] 60-65 parts of fluorocarbon resin

[0011] 20-25 parts acrylic resin

[0012] 10-15 parts polyester resin

[0013] Wherein, nano titanium dioxide particles are dispersed in the fluorocarbon resin;

[0014] In the acrylic resin, short glass fibers are dispersed;

[0015] Graphene oxide is dispersed in the polyester resin;

[0016] The nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 10-20nm;

[0017] The aspect ratio of the glass fiber staple is 10:1-15:1, and the average length is 1.2-1.8 mm;

[0018] The D50 of the graphene oxide is 80-150nm.

[0019] In the above technical scheme, by using a variety of resins to compound with fluorocarbon resin, specifically, by compounding with acrylic resin and polyester resin, the toughness of the paint film formed by the fluorocarbon resin on the surface of the aluminum alloy substrate is adjusted to achieve a toughening effect; in addition, the inventors found that by adding fillers of different morphologies to the compounded resin system, specifically, including granular nano-titanium dioxide, fibrous glass fiber staple fibers, and graphene oxide with a lamellar structure, the paint film formed by the fluorocarbon resin has a higher density, so that the paint film can resist the erosion of substances such as water and air to the inside of the paint film during long-term use, so that it can be attached to the surface of the aluminum alloy substrate for a long time; in addition, the inventors surprisingly found that by first dispersing nano-titanium dioxide particles in fluorocarbon resin, dispersing glass fiber staple fibers in acrylic resin, and dispersing graphene oxide in polyester resin, the overall paint film can be more uniform after film formation, so that it is not easy to have local shedding failure, thereby effectively ensuring the integrity of the paint film.

[0020] Furthermore, in the fluorocarbon resin, the content of the nano titanium dioxide particles is 6-8% of the mass of the fluorocarbon resin; in the acrylic resin, the content of the glass fiber staple is 10-12% of the mass of the acrylic resin; in the polyester resin, the content of the graphene oxide is 3-5% of the mass of the polyester resin.

[0021] Furthermore, in the fluorocarbon resin, the content of the nano titanium dioxide particles is 7% of the mass of the fluorocarbon resin; in the acrylic resin, the content of the glass fiber staple is 11% of the mass of the acrylic resin; in the polyester resin, the content of the graphene oxide is 3.5% of the mass of the polyester resin.

[0022] Furthermore, the sphericity of the quasi-spherical nano-titanium dioxide is 8.0-8.5.

[0023] When nano titanium dioxide with a certain sphericity is mixed with other components of corresponding specifications and mass ratios, the product can have excellent fluidity during processing and spraying, so that it can be evenly spread on the surface of the substrate, which is conducive to obtaining a uniform and dense coating.

[0024] Furthermore, a phthalate coupling agent is adsorbed on the surface of the nano titanium dioxide particles; and a silane coupling agent is adsorbed on the surface of the glass fiber staple fibers.

[0025] Furthermore, the phthalate coupling agent is selected from any one of KR-138S pyrophosphate phthalate coupling agent and KR-212S chelate 200 phthalate coupling agent.

[0026] Furthermore, the silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.

[0027] A method for preparing a fluorocarbon powder coating, the specific preparation steps comprising:

[0028] dispersing nano titanium dioxide in fluorocarbon resin to obtain pretreated fluorocarbon resin;

[0029] Dispersing glass fiber staple fibers in acrylic resin to obtain pretreated acrylic resin;

[0030] dispersing graphene oxide in polyester resin to obtain pretreated polyester resin;

[0031] After weighing the raw materials according to the formula, the raw materials are mixed evenly, and then extruded, crushed and sieved by a twin-screw extruder to obtain a fluorocarbon powder coating product. DETAILED DESCRIPTION

[0032] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0033] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0034] Example 1

[0035] Select MB-2952 acrylic resin produced by Mitsubishi of Japan, and disperse 10% of the mass of glass fiber short fibers in the acrylic resin to obtain pretreated acrylic resin;

[0036] Before dispersing the glass fiber short fibers in the acrylic resin, the glass fiber short fibers are first dispersed in an ethanol solution with a mass fraction of 80%, and then a silane coupling agent with a mass fraction of 5% of the glass fiber short fibers is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the silane coupling agent on the surface of the glass fiber short fibers;

[0037] The aspect ratio of the glass fiber short fibers is 10:1, and the average length is 1.2 mm.

[0038] The silane coupling agent is selected from silane coupling agent KH-550;

[0039] Selecting a polyester resin of model P3950 produced by Zhejiang Chuanhua Chemical Group, and dispersing 3% by mass of graphene oxide in the polyester resin to obtain a pretreated polyester resin;

[0040] Wherein, the D50 of the graphene oxide is 80nm;

[0041] Selecting PVDF as the fluorocarbon resin, and dispersing 6% of the mass of the fluorocarbon resin in the PVDF as nano-titanium dioxide particles to obtain a pretreated fluorocarbon resin;

[0042] Before dispersing the nano titanium dioxide particles in the fluorocarbon resin, the nano titanium dioxide is first dispersed in an ethanol solution with a mass fraction of 80%, and then a phthalate coupling agent with a mass fraction of 5% of the nano titanium dioxide is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the phthalate coupling agent on the surface of the nano titanium dioxide;

[0043] Wherein, the nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 10 nm;

[0044] The sphericity of the quasi-spherical nano-titanium dioxide is 8.0;

[0045] The phthalate coupling agent is selected from KR-138S pyrophosphate phthalate coupling agent;

[0046] In terms of weight, 60 parts of pretreated fluorocarbon resin, 20 parts of pretreated acrylic resin, 10 parts of pretreated polyester resin, 1 part of leveling agent, 1.2 parts of defoaming agent, and 5 parts of barium sulfate are taken in turn, and the raw materials of each component of the formula are uniformly mixed according to the formula ratio, and uniformly crushed in a grinder, and the components are mixed and extruded using a twin-screw extruder, followed by deep-cold crushing and passing through a 180-mesh sieve to obtain a powder coating product.

[0047] Example 2

[0048] Select MB-2952 acrylic resin produced by Mitsubishi of Japan, and disperse 11% of glass fiber staple fibers by weight of the acrylic resin therein to obtain a pretreated acrylic resin;

[0049] Before dispersing the glass fiber short fibers in the acrylic resin, the glass fiber short fibers are first dispersed in an ethanol solution with a mass fraction of 80%, and then a silane coupling agent with a mass fraction of 5% of the glass fiber short fibers is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the silane coupling agent on the surface of the glass fiber short fibers;

[0050] The aspect ratio of the glass fiber staple is 12:1, and the average length is 1.5 mm.

[0051] The silane coupling agent is selected from silane coupling agent KH-560;

[0052] Selecting a polyester resin of model P3950 produced by Zhejiang Chuanhua Chemical Group, and dispersing 3.5% by mass of graphene oxide in the polyester resin to obtain a pretreated polyester resin;

[0053] Wherein, the D50 of the graphene oxide is 100nm;

[0054] Selecting PVDF as the fluorocarbon resin, and dispersing 7% of the mass of the fluorocarbon resin in the PVDF as nano-titanium dioxide particles to obtain a pretreated fluorocarbon resin;

[0055] Before dispersing the nano titanium dioxide particles in the fluorocarbon resin, the nano titanium dioxide is first dispersed in an ethanol solution with a mass fraction of 80%, and then a phthalate coupling agent with a mass fraction of 5% of the nano titanium dioxide is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the phthalate coupling agent on the surface of the nano titanium dioxide;

[0056] Wherein, the nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 15nm;

[0057] The sphericity of the quasi-spherical nano titanium dioxide is 8.2;

[0058] The phthalate coupling agent is selected from KR-138S pyrophosphate phthalate coupling agent;

[0059] In terms of weight, 62 parts of pretreated fluorocarbon resin, 23 parts of pretreated acrylic resin, 12 parts of pretreated polyester resin, 1 part of leveling agent, 1.2 parts of defoaming agent, and 5 parts of barium sulfate are taken in turn, and the raw materials of each component of the formula are uniformly mixed according to the formula ratio, and uniformly crushed in a grinder, and the components are mixed and extruded using a twin-screw extruder, followed by deep-cold crushing and passing through a 180-mesh sieve to obtain a powder coating product.

[0060] Example 3

[0061] Select MB-2952 acrylic resin produced by Mitsubishi of Japan, and disperse 10-12% of glass fiber staple fibers by weight of the acrylic resin therein to obtain pretreated acrylic resin;

[0062] Before dispersing the glass fiber short fibers in the acrylic resin, the glass fiber short fibers are first dispersed in an ethanol solution with a mass fraction of 80%, and then a silane coupling agent with a mass fraction of 5% of the glass fiber short fibers is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the silane coupling agent on the surface of the glass fiber short fibers;

[0063] The aspect ratio of the glass fiber staple is 15:1, and the average length is 1.8 mm.

[0064] The silane coupling agent is selected from silane coupling agent KH-570;

[0065] Selecting a polyester resin of model P3950 produced by Zhejiang Chuanhua Chemical Group, and dispersing 5% by mass of graphene oxide in the polyester resin to obtain a pretreated polyester resin;

[0066] Wherein, the D50 of the graphene oxide is 150nm;

[0067] Selecting PVDF as the fluorocarbon resin, and dispersing 8% of the mass of the fluorocarbon resin in the PVDF as nano-titanium dioxide particles to obtain a pretreated fluorocarbon resin;

[0068] Before dispersing the nano titanium dioxide particles in the fluorocarbon resin, the nano titanium dioxide is first dispersed in an ethanol solution with a mass fraction of 80%, and then a phthalate coupling agent with a mass fraction of 5% of the nano titanium dioxide is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the phthalate coupling agent on the surface of the nano titanium dioxide;

[0069] Wherein, the nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 20nm;

[0070] The sphericity of the quasi-spherical nano-titanium dioxide is 8.5;

[0071] The phthalate coupling agent is selected from KR-212S chelated 200 type phthalate coupling agent;

[0072] In terms of weight, 65 parts of pretreated fluorocarbon resin, 25 parts of pretreated acrylic resin, 15 parts of pretreated polyester resin, 1 part of leveling agent, 1.2 parts of defoaming agent, and 5 parts of barium sulfate are taken in turn, and the raw materials of each component of the formula are uniformly mixed according to the formula ratio, and uniformly crushed in a grinder, and the components are mixed and extruded using a twin-screw extruder, followed by deep-cold crushing and passing through a 180-mesh sieve to obtain a powder coating product.

[0073] Example 4

[0074] Select MB-2952 acrylic resin produced by Mitsubishi of Japan, and disperse 10% of the mass of glass fiber short fibers in it to obtain pretreated acrylic resin;

[0075] Before dispersing the glass fiber short fibers in the acrylic resin, the glass fiber short fibers are first dispersed in an ethanol solution with a mass fraction of 80%, and then a silane coupling agent with a mass fraction of 5% of the glass fiber short fibers is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the silane coupling agent on the surface of the glass fiber short fibers;

[0076] The aspect ratio of the glass fiber short fibers is 10:1, and the average length is 1.2 mm.

[0077] The silane coupling agent is selected from silane coupling agent KH-550;

[0078] Selecting a polyester resin of model P3950 produced by Zhejiang Chuanhua Chemical Group, and dispersing 3% by mass of graphene oxide in the polyester resin to obtain a pretreated polyester resin;

[0079] Wherein, the D50 of the graphene oxide is 80nm;

[0080] Selecting PVDF as the fluorocarbon resin, and dispersing 6% of the mass of the fluorocarbon resin in the PVDF as nano-titanium dioxide particles to obtain a pretreated fluorocarbon resin;

[0081] Before dispersing the nano titanium dioxide particles in the fluorocarbon resin, the nano titanium dioxide is first dispersed in an ethanol solution with a mass fraction of 80%, and then a phthalate coupling agent with a mass fraction of 5% of the nano titanium dioxide is added, and after stirring for 2 hours, the mixture is filtered and dried to adsorb the phthalate coupling agent on the surface of the nano titanium dioxide;

[0082] Wherein, the nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 10 nm;

[0083] The sphericity of the quasi-spherical nano-titanium dioxide is 7.5;

[0084] The phthalate coupling agent is selected from KR-138S pyrophosphate phthalate coupling agent;

[0085] In terms of weight, 60 parts of pretreated fluorocarbon resin, 20 parts of pretreated acrylic resin, 10 parts of pretreated polyester resin, 1 part of leveling agent, 1.2 parts of defoaming agent, and 5 parts of barium sulfate are taken in turn, and the raw materials of each component of the formula are uniformly mixed according to the formula ratio, and uniformly crushed in a grinder, and the components are mixed and extruded using a twin-screw extruder, followed by deep-cold crushing and passing through a 180-mesh sieve to obtain a powder coating product.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that graphene oxide is not added, and other conditions remain unchanged.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that no pre-treated polyester resin is added, and other conditions remain unchanged.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that no glass fiber staple is added, and other conditions remain unchanged.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 1 is that no pre-treated acrylic resin is added, and other conditions remain unchanged.

[0094] Comparative Example 5

[0095] The difference between this comparative example and Example 1 is that no nano titanium dioxide particles are added, and the other conditions remain unchanged.

[0096] The performance tests were performed on the products obtained in Examples 1-4 and Comparative Examples 1-5. The specific test methods and test results are as follows:

[0097] A 6 series aluminum alloy was selected as the substrate. After the surface was degreased, the product obtained in the embodiment or the comparative example was sprayed on the substrate surface by an electrostatic spraying process, and then cured at 200° C. for 15 minutes, and then the following coating test was performed;

[0098] The adhesion test was conducted using the 100-grid test method to observe the coating shedding;

[0099] The above adhesion test is carried out after the coating is aged by B lamp. Specifically, during B lamp aging, the coating is irradiated continuously for 24 rounds with a cycle of 10 days.

[0100] In addition, the glossiness of the coating was tested before and after the B-light aging, and the specific test results are shown in Table 1;

[0101] Table 1: Product performance test results

[0102] Adhesion test results Glossiness before aging / % Gloss after aging / % Example 1 No shedding and hollowing 38.2% 35.5% Example 2 No shedding and hollowing 41.5% 39.9% Example 3 No shedding and hollowing 39.5% 34.5% Example 4 3% area loss 35.6% 30.1% Comparative Example 1 12% area loss 31.5% 21.0% Comparative Example 2 18% area loss 30.1% 19.5% Comparative Example 3 10% area shedding 32.2% 20.6% Comparative Example 4 15% area loss 29.8% 18.9% Comparative Example 5 9% area fell off 31.2% 19.6%

[0103] It can be seen from the test results in Table 1 that the product obtained by the present invention has excellent adhesion to the aluminum alloy substrate and can still maintain good gloss after aging.

[0104] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A fluorocarbon powder coating, characterized in that: The invention comprises the following raw materials in parts by weight: 60-65 parts of fluorocarbon resin 20-25 parts acrylic resin 10-15 parts polyester resin Wherein, nano titanium dioxide particles are dispersed in the fluorocarbon resin; In the acrylic resin, short glass fibers are dispersed; Graphene oxide is dispersed in the polyester resin; The nano titanium dioxide particles are spherical nano titanium dioxide particles, and the D50 of the nano titanium dioxide particles is 10-20nm; The aspect ratio of the glass fiber staple is 10:1-15:1, and the average length is 1.2-1.8 mm; The D50 of the graphene oxide is 80-150nm; Wherein, the preparation method of the fluorocarbon powder coating comprises the following steps: dispersing nano titanium dioxide in fluorocarbon resin to obtain pretreated fluorocarbon resin; Dispersing glass fiber staple fibers in acrylic resin to obtain pretreated acrylic resin; dispersing graphene oxide in polyester resin to obtain pretreated polyester resin; After weighing the raw materials according to the formula, mix them evenly, extrude them through a twin-screw extruder, crush them, and sieve them to obtain fluorocarbon powder coating products; The sphericity of the quasi-spherical nano titanium dioxide is 8.0-8.5; In the fluorocarbon resin, the content of the nano titanium dioxide particles is 6-8% of the mass of the fluorocarbon resin; in the acrylic resin, the content of the glass fiber staple is 10-12% of the mass of the acrylic resin; in the polyester resin, the content of the graphene oxide is 3-5% of the mass of the polyester resin.

2. A fluorocarbon powder coating according to claim 1, characterized in that: In the fluorocarbon resin, the content of the nano titanium dioxide particles is 7% of the mass of the fluorocarbon resin; in the acrylic resin, the content of the glass fiber staple is 11% of the mass of the acrylic resin; in the polyester resin, the content of the graphene oxide is 3.5% of the mass of the polyester resin.

3. A fluorocarbon powder coating according to claim 1, characterized in that: The surface of the nano titanium dioxide particles is adsorbed with a phthalate coupling agent; the surface of the glass fiber staple fibers is adsorbed with a silane coupling agent.

4. A fluorocarbon powder coating according to claim 3, characterized in that: The phthalate coupling agent is selected from any one of KR-138S pyrophosphate phthalate coupling agent and KR-212S chelate 200 phthalate coupling agent.

5. A fluorocarbon powder coating according to claim 3, characterized in that: The silane coupling agent is selected from any one of silane coupling agent KH-550, silane coupling agent KH-560 or silane coupling agent KH-570.

Citation Information

Patent Citations

  • Ultra-weather-resistant powder coating

    CN102838925A

  • Fluorocarbon powder coating for outdoor iron towers, and preparation method thereof

    CN110776794A